Study on the characteristics of horn-like vortices in an axial flow pump impeller under off-design conditions. Issue 1 (1st January 2021) - Zhao, Haoru; Wang, Fujun; Wang, Chaoyue; Chen, Wenhao; Yao, Zhifeng; Shi, Xiaoyan; Li, Xiaoqin; Zhong, Qiang
Abstract : The dominant vortex structure near the hub in rotor corner separation flow has an important influence on the internal flow of the axial flow rotating machinery. However, the current quantitative research on the key vortical characteristics of the dominant vortex structure in the corner separation flow is still insufficient. The analysis of the dominant vortex structure (horn-like vortex) in an axial flow pump was conducted and found that the average vortex intensity and turbulence eddy dissipation show a gradual weakening trend along the vortex core line from the corner region to the vortex tail under various working conditions. The evolution of the horn-like vortex in a life cycle includes five stages, inception-growth-development-attachment-decay in the typical working condition 0.62 Q 0 . The statistical average frequency of the periodic evolution is about 2.76 times the shaft rotation frequency. The pressure fluctuation near the hub induced by the horn-like vortex increases rapidly and dominates in the flow channel. The average peak-peak value on the impeller outlet section close to the horn-like vortex is about 2.79 times that of the impeller inlet section and should be paid enough attention to.